PENERAPAN MODEL DUTI-DUTA UNTUK MELATIH KETERAMPILAN BERBICARA SISWA PADA PEMBELAJARAN AGAMA KRISTEN KELAS VB SDN 143 INPRES GE’TENGAN - Marianti Pabia; Samuel Joni, Afrianto Lopo, Viola Valengsa, Yohanis Tarru (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
Research with the title "Application of the Duti-Duta Model to train students' speaking skills in Christian Religion class VB SDN 143 INPRES Ge'tengan". The purpose of this study is to describe how the Duti-Duta model is applied in training students' speaking skills in Christian Religion class Vb SDN 143 Inpres Ge'tengan. In this study, the authors used a research method, namely Classroom Action Research (CAR), the source of the data was obtained from informants, namely PAK teachers and students studying literature and field studies. By using data collection techniques by observation using pre-test and using documentation. Data analysis techniques, namely data reduction, data exposure and drawing conclusions. From the results of the study, it can be concluded that the Duti-Duta model in Christian Religious Education learning can train speaking skills at SDN 143 Inpres Ge'tengan. This can be seen from the learning outcomes of students in cycle I where the average value was 71.31%, cycle II the average value of students was 82.81% then cycle III the average value of students increased, reaching 85 .43%.